THE EFFECT OF MORINGA OLEIFERA LEAF FLOUR SUBSTITUTION ON BROILER CHICKEN CARCASS PRODUCTION - Nurhalifah; Mulyadi; Dedhi Yustendi; Zulkifli (Jurnal Penelitian Progresif, 2026)
Moringa leaves ( Moringa oleifera ) are plants that have high nutritional content, including protein, calcium, vitamin C, iron, and bioactive compounds such as flavonoids and phenolics that function as natural antioxidants. These contents make Moringa leaves potential as an alternative ingredient in poultry feed, especially broiler chickens, to support the immune system while improving carcass quality. This study aims to determine the effect of Moringa oleifera leaf flour substitution in rations on broiler chicken carcass production which will be carried out in Bueng Sidom Village, Blang Bintang District, Aceh Besar Regency using a Completely Randomized Design with four treatments and four replications. The treatments consisted of P0 (100% commercial ration), P1 (97% commercial ration + 3% moringa leaf flour), P2 (94% commercial ration + 6% moringa leaf flour), and P3 (91% commercial ration + 9% moringa leaf flour). The parameters observed included live weight, carcass weight, carcass percentage, and percentage of carcass parts such as thighs, wings, and breasts . Data were analyzed using SPSS 22. The results showed that substitution of moringa leaf flour up to 9% did not have a significant effect on all parameters observed statistically. However, descriptively there were variations in the trend of results in each treatment. P2 showed the best value for live weight and carcass weight, P1 for carcass and wing percentage, P0 for thigh percentage, and P3 for breast percentage. In conclusion, substitution of moringa leaf flour in broiler chicken rations did not have a significant effect on carcass performance, so the null hypothesis (H0) was accepted. Nevertheless, this study provides an initial overview of the potential of moringa leaves as a highly nutritious natural feed ingredient for broiler chickens.